Isolation, Characterization, and Antioxidant Activity Evaluation of a Fucoidan from an Enzymatic Digest of the Edible Seaweed, Hizikia fusiforme - Lei Wang; Thilina U. Jayawardena; Hye-Won Yang; Hyo Geun Lee; Min-Cheol Kang; K. K. Asanka Sanjeewa; Jae Young Oh; You-Jin Jeon (MDPI AG, 2020)
The previous study suggested that the sulfated polysaccharides from Hizikia fusiforme (HFPS) possess strong antioxidant activity. The purpose of this study is to isolate fucoidan from HFPS and to investigate its antioxidant activity. A fucoidan (HFPS-F4) with a molecular weight of 102.67 kDa was isolated from HFPS. HFPS-F4 contains 99.01% of fucoidan (71.79 ± 0.56% of carbohydrate and 27.22 ± 0.05% of sulfate content). The fucoidan increased the viability of H2O2-treated Vero cells by 5.41, 11.17, and 16.32% at the concentration of 12.5, 25, and 50 μg/mL, respectively. Further results demonstrated that this effect act diminishing apoptosis by scavenging intracellular reactive oxygen species (ROS) via increasing the expression of the endogenous antioxidant enzymes, which was induced by elevating total nuclear factor (erythroid-derived 2)-like 2 (Nrf2) levels. In addition, the in vivo test results displayed that the pretreatment of fucoidan improved the survival rates and decreased heart-beating rate, ROS, cell death, and lipid peroxidation in H2O2-stimulated zebrafish. Taken together, these results demonstrated that fucoidan isolated from HFPS has strong in vitro and in vivo antioxidant activities and it could be utilized in pharmaceutical, nutraceutical, and cosmeceutical industries.